What Makes Persistent Identifiers Persistent? - Nikos Askitas (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2010)
This essay sketches technical and non-technical issues around persistent identifiers (henceforth PIs) in a manner which makes no attempt to be complete. Our goal is to rescue the core notions from the obscurity which detail and completeness burdens them with. A reader willing to entertain the idea of their necessity should be able to cut to the chase and follow a more complex and involved debate after reading this. Our hope is that in isolating the core issues we will enable a more founded discussion of the social and political issues involved in PIs.
Keywords: 330; Persistent Identifier; handle; DOI; data; trust; URN; RePEc